Application of Science and Technology in Waste Management, Digital Marketing-Branding Strategies, and Accounting Systems for Environmentally Friendly Fertilisers and Recycled Products - IMANINGSIH, Erna Sofriana; SUPRIHATININGSIH, Wiwit; SETIYAWATI, Hari; PUTRA, Rangga Aji; SALMAN, Kina Bahru; ARIYANTO , Satrio Muhammad (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
This PKM was carried out by the UMB team in partnership with the Nurul Yaqin Recitation Group, Parigi Baru Village, Pondok Aren District, South Tangerang, and was funded by DRTPM DIKTI through the PPM Grant Program for the 2024 fiscal year scheme. The Nurul Yaqin Recitation Group has 19 members; apart from being homemakers, they also have informal workers and small home industry businesses. This recitation group carries out its routine activities, namely conducting religious studies under the care of the DKM Masjid Baitul Mukminin. It is active in various community activities and can mobilize other community members through activities. Therefore, they have the potential to be pioneers among grassroots communities to change people's lifestyles for the better through the green movement in their area. The problems experienced by partners are: 1) the accumulation of organic and inorganic waste in the area around their residence has not been appropriately managed, 2) There is no utilization of business opportunities for compost and recycled crafts, 3) There is no accounting application system to record transactions and financial reporting from the production of liquid fertilizer and solid fertilizer and the recycling of inorganic waste. The solutions offered are: 1) Provide training and counseling related to processing organic and inorganic waste into valuable products 2) Provide training related to digital marketing strategies 3) Provide training related to recording transactions and financial reporting through accounting software applications.